GAGASAN MOESLIM ABDURRAHMAN TENTANG PENDIDIKAN ISLAM TRANSFORMATIF Moeslim Abdurrahman’s Ideas About Transformative Islamic Education - Mohamad Ali; Ma'arif Jamuin (Balai Penelitian dan Pengembangan Agama Semarang, 2017)
The concepts of Islamic education in Indonesia are still little developed in the discussion of educational theories. One concept that has not paid much attention yet is transformative Islamic education. This study aims to identify the locus of Transformative Islamic Education (PIT) in the thought currents of contemporary Indonesian Islamic education, and compose Moeslim Abdurrahman’s ideas sketch on it based on the education system. It uses qualitative research and literature data analyzed by content analysis. The findings of this study are that the transformative tendency arises from the essential-traditionalist and progressive-modernist who call for the transformation of social life as a whole. Thus, the goal of this transformative Islamic education is to create critical and dialogical learners who are actively involved in the process of social transformation as the task of the caliphate.